Rebuilding Life: The Resilience of Widows After the Loss of Their Husbands - Isnaini, Ulvi; Widiantoro, FX Wahyu; Syariful, Syariful (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Losing a spouse is a deeply emotional and complex experience, especially for elderly women who often face psychological, social, and cultural challenges simultaneously. This study aims to explore the resilience dynamics of elderly widows after the loss of their husbands, focusing on how they manage emotions and rebuild their lives. Using a qualitative method with a phenomenological approach, the study involved four female participants aged 60 and above living in Tirta Buana Village. Data were collected through in-depth interviews and unstructured observations, then analyzed thematically. The findings reveal that these widows demonstrate high levels of resilience through strategies such as emotional regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and willingness to seek support. Internal factors such as spirituality and coping abilities, as well as external factors such as support from family and the community, significantly contributed to their recovery process. This research underscores the need for policies that are more sensitive to the psychosocial needs of widows and highlights the importance of creating supportive, stigma-free social spaces. The results are expected to serve as a foundation for further studies and the development of more holistic interventions aimed at improving the well-being of elderly widows.Kehilangan pasangan hidup merupakan pengalaman yang sangat emosional dan kompleks, terutama bagi wanita lanjut usia yang sering kali menghadapi tantangan psikologis, sosial, dan budaya secara bersamaan. Penelitian ini bertujuan untuk memahami dinamika resiliensi janda lanjut usia pasca kehilangan suami, dengan fokus pada bagaimana mereka mengelola emosi dan membangun kembali kehidupan mereka. Penelitian menggunakan metode kualitatif dengan pendekatan fenomenologi, melibatkan empat subjek berusia 60 tahun ke atas yang berdomisili di Desa Tirta Buana. Data dikumpulkan melalui wawancara mendalam dan observasi tidak terstruktur, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa para janda menunjukkan tingkat resiliensi yang tinggi melalui strategi seperti regulasi emosi, kontrol dorongan, optimisme, analisis sebab-akibat, empati, efikasi diri, serta kemauan untuk mencari dukungan. Faktor internal seperti spiritualitas dan kemampuan koping, serta faktor eksternal seperti dukungan keluarga dan komunitas, memainkan peran penting dalam mempercepat proses pemulihan. Penelitian ini mengindikasikan perlunya kebijakan yang lebih sensitif terhadap kebutuhan psikososial janda, serta pentingnya menciptakan ruang sosial yang suportif dan bebas stigma. Temuan ini diharapkan dapat menjadi landasan bagi studi lanjutan dan pengembangan intervensi yang lebih holistik untuk meningkatkan kesejahteraan janda di usia lanjut.